Motives, governance, and long-term performance of mergers and acquisitions in Asia - Puspita Rani; Elvia R. Shauki; Darminto Darminto; Ruslan Prijadi (Cogent Business & Management, 2020)
This study aims to examine the long-term performance of post-Mergers and Acquisitions (M&A) based on the motive's category. This study also examines whether the governance at firm-level and country-level affects the relationship between motives and long-term performance of M&A. This study uses a sample of 301 completed M&A transactions of Asian companies in 11 countries from 2002 to 2012 and analyses the data using the cross-sectional moderated regression method. This study measures and categorizes M&A motives into synergy and agency categories using two alternate ways, which first using the stock market reaction data of acquirer and target at the M&A announcement period estimated by applying an event study methodology, and the second using the combination of the stock market reaction data and some accounting variables through logistic regression analysis. This study finds that synergy-motivated M&A results in significantly higher long-term performance post-M&A than agency-motivated M&A. It also proves that the positive effect of M&A motives on the long-term performance post-M&A is significantly higher when companies have better firm-level governance quality, but a similar result cannot be proved for country-level governance. This study provides a cross-country M&A study in the Asian region that has an essential role in global M&A activity in recent years. Considering the possibility of changes in company structure and environment post-M&A, this study contributes to provides an insight related to the role of the governance quality post-M&A as a monitoring tool in the realization of M&A predicted gain that can improve M&A performance.
Keywords: 650; M&A motives; long-term performance; governance; synergy motives; agency motives